An Alternative Transseptal Intracardiac Echocardiography Strategy to Guide Left Atrial Appendage Closure: The First Described Case. (4th August 2014) - FASSINI, GAETANO; RUSSO, ANTONIO DELLO; CONTI, SERGIO; TONDO, CLAUDIO
Transseptal Intracardiac Echocardiography Strategy Transesophageal echocardiography (TEE) is the standard imaging technique to guide device implantation for left atrial appendage (LAA) closure. Unfortunately, TEE was contraindicated in this patient due to the high risk of variceal hemorrhage. Critical information about the exact anatomic characteristics of the LAA can be obtained using intracardiac echocardiography (ICE). However, standard right‐side views do not allow a complete visualization of the LAA: in particular, a reliable left circumflex coronary artery short axis view, relevant for device positioning, is not always achievable. Transseptal views of the LAA with ICE might be used in planning an appropriate intervention strategy for patients who are not suitable for TEE imaging.